New face of regional integration in Latin America and the Caribbean - Iglesias, Enrique V. ([World Bank] [Washington]US, 1997)
Overviews the issue of regional integration in Latin America and the Caribbean. Focuses on broader trade issues and the overall process of policy change in the region. Discusses the role of the Inter-American Development Bank.